Rhymed Officium about St. Catherine in the 12th-Century Płock Pontifical - Piotr Wiśniewski (The Francis de Sales Scientific Society (TNFS.PL), 2022)
Pontificale Plocense from the 12th-century is one of the first Polish pontificals entirely preserved to this day. Among liturgical ceremonials, there is a rhymed officium about St. Catherine of Alexandria. Its music bears some explicitly characteristic features of the late Middle Ages monody. A condensed musical style reveals a departure from the initial esthetic assumptions and it presents another possibility of performing the Gregorian chant. This officium, apart from following the compositional principles prevailing in Europe at that time, provides evidence that the Middle Ages were also an era seeking new forms of expression.